Sequential interventions to maintain the safety and service provisions of human milk banking in India: keeping up with the call to action in response to the COVID-19 pandemic - Maheshwar Bhasin; Sushma Nangia; Gunjana Kumar; Abha Parihar; Srishti Goel (BMC, 2022)
Abstract Background WHO recommends donor milk as the next best choice if Mothers' own milk (MOM) is unavailable. At our milk bank, during the COVID 19 pandemic, we observed a steep decline in the collection of donor milk, while Pasteurised Donor human milk (PDHM) demand increased. This called for active intervention. Methods We employed the quasi-experimental quality improvement initiative. During September 2020 (baseline period) the team members identified modifiable bottlenecks and suggested interventions (using WhatsApp to increase follow up, telehealth and digital tools) which were implemented in October 2020 and the impact was evaluated till March 2021. The SMART aim was "to meet the demand (estimated as 15,000 ml/month) of donor milk for adjoining 80-bedded NICU". Process measures were; daily amount of donor milk collected, pasteurized donor milk disbursed to NICU, number of donors and frequency of donations. The balancing measure was that the collection of donor milk should not undermine the provision of freshly expressed MOM for babies. Results Collection of donor milk increased by 180% from baseline during the Intervention phase. This was sustained throughout the sustenance phase (November 2020 and March 2021) with an average monthly collection of 16,500 ml. Strikingly, the increased follow-up of mothers with emphasis on MOM decreased the NICU's donor milk requirement from 13,300 ml (baseline) to 12,500 ml (intervention) to 8,300 ml (sustenance). Monitoring of daily MOM used in the NICU revealed a 32% surge from 20,000 ml (baseline) to 27,000 ml (intervention) sustained at 25,000 ml per month. Conclusion By improving the provisions of human milk banks, near-exclusive human milk feeding can be ensured even during the pandemic time.